(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Eggshell is solid wastes produced from the food industry. Commonly, eggshell and its membrane used to treat water pollution such as heavy metal removal and also dye removal. Thus, on the treatment process, it’s was having the material handling problem, which was needed filtration method to remove out the adsorbent from the solution, and it was not efficient when commercializing in the wastewater treatment plant. Therefore, this study was using alcohol-sodium alginate (PVA/SA) to encapsulate the eggshell membrane, and this encapsulation method also would be able to enhance the performance of raw material on the dye adsorption. In this study, the eggshell membrane (ESM) are prepared in bead form, and the optimization of the bead are performed by the removal of congo red dye at several parameters such as pH, initial dye concentration, contact time, and dosage of ESM. The central composite design was selected to optimize the adsorption process by generating 30 runs of the experiment using software Design Expert® version 11. The Fourier Transforms Infrared Spectroscopy (FTIR) analysis and Brunauer-Emmett-Teller (BET) analysis are used to characterize the ESM bead. There was found out that main functional group on ESM bead contribute on adsorption process were carbonyl group, hydroxyl group and ESM bead also having the 42.74 nm of pore size. The optimize point for each parameter was 12.63mg/L of initial dye concentration, 6.12 g of ESM dosage, pH 2.19 and 12.83 min of contact time and the optimum congo red dye removal efficiency was 98.86 %.